The influence of micronutrients and macronutrients excess or deficiency on thyroid function - K. Brzdęk; S. Wiśniewski; O. Domańska; W. Baran; M. Brzdęk (The Ukrainian Biochemical Journal)
The thyroid gland’s functionality is complex and is influenced by a variety of compounds, notably iodine, selenium, iron, calcium, thiamine (vitamin B1), vitamin B12 and vitamin D. This study aims to elucidate the significance of micronutrients and macronutrients in the functioning of the thyroid gland and explore how nutrient imbalances may lead to various thyroid disorders, including thyroid cancer.